miR-137 confers robustness to the territorial restriction of the neural plate border - Scatturice, Luciana Ailín (2024)
The neural plate border (NPB) of vertebrate embryos is segregated from the neural plate (NP) and epidermal regions, and comprises an intermingled group of progenitors with multiple fate potential. Recent studies have shown that, during the gastrula stage, TFAP2A acts as a pioneer factor in remodeling the epigenetic landscape required to activate components of the NPB induction program. Here, we show that chick Tfap2a has two highly conserved binding sites for miR-137, and both display a reciprocal expression pattern at the NPB and NP, respectively. In addition, ectopic miR-137 expression reduced TFAP2A, whereas its functional inhibition expanded their territorial distribution overlapping with PAX7. Furthermore, we demonstrate that loss of the de novo DNA methyltransferase DNMT3A expanded miR-137 expression to the NPB. Bisulfite sequencing revealed a markedly elevated presence of non-canonical CpH methylation within the miR-137 promoter region when comparing NPB and NP samples. Our findings show that miR-137 contributes to the robustness of NPB territorial restriction in vertebrate development.